Classroom assessment techniques: an assessment and student evaluation method - Walker, Dawn-Marie (Scientific Research Publishing, 2012)
Some of the challenges that face Higher Education are how to ensure that assessment is meaningful and that feedback is prompt in order to promote learning. Another issue is how to provide lecturers with feedback regarding their efficacy, in a timely and non-judgmental manner. This paper proposes that Classroom Assessment Techniques (Angelo and Cross, 1993), maybe a good way of answering both of those issues. They are quick and easy tasks set within the lecture, which tests the student’s knowledge, providing an immediate opportunity for further elaboration if needed by the lecturer, therefore providing immediate feedback to the students. It also ensures that the lecturer has delivered the most salient messages, therefore also providing feedback to the lecturer.